2021
DOI: 10.48550/arxiv.2107.03821
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Edge Sampling and Graph Parameter Estimation via Vertex Neighborhood Accesses

Abstract: We consider the problems from sublinear algorithms of sampling and counting edges from a graph on n vertices where our basic access is via uniformly sampled vertices. When we have accessed a vertex, we can see its degree, and we can access its neighbors, e.g., one picked uniformly at random. Accessing as few vertices as possible we want to sample and count edges. To appreciate our bounds below, note that if we have a graph with isolated vertices and a clique of size around √ m, then it takes Ω( n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…When a graph G = (V, E) is very large, we may want to approximately solve certain tasks without looking at the entire G, thus having a time complexity that is sublinear in the size of G. In particular, estimating global properties of G such |V | or |E| in this setting is an important problem and has been studied in both theoretical and applied communities [4,5,6,8,10,14,16]. Since the algorithm does not have the time to pre-process (or even see) the whole graph, it is important to specify how we access G. Several models are employed in the literature.…”
Section: This Papermentioning
confidence: 99%
See 2 more Smart Citations
“…When a graph G = (V, E) is very large, we may want to approximately solve certain tasks without looking at the entire G, thus having a time complexity that is sublinear in the size of G. In particular, estimating global properties of G such |V | or |E| in this setting is an important problem and has been studied in both theoretical and applied communities [4,5,6,8,10,14,16]. Since the algorithm does not have the time to pre-process (or even see) the whole graph, it is important to specify how we access G. Several models are employed in the literature.…”
Section: This Papermentioning
confidence: 99%
“…Currently, the best known algorithm is the one by Eden, Ron and Seshadhri [5] and has complexity Õ( n ε 2 √ m ). If pair queries are allowed, the algorithm of Tětek and Thorup [16] has complexity Õ( n ε √ m + 1 ε 4 ); in the same paper the authors showed a lower bound which is near-matching for ε ≥ m 1/6 /n 1/3 as well as an algorithm with complexity Õ(…”
Section: This Papermentioning
confidence: 99%
See 1 more Smart Citation